Host inflammatory dynamics reveal placental immune modulation by Group B Streptococcus during pregnancy - Felicia Kuperwaser; Gal Avital; Michelle J Vaz; Kristen N Noble; Allison N Dammann; Tara M Randis; David M Aronoff; Adam J Ratner; Itai Yanai (Molecular Systems Biology)
Abstract Group B Streptococcus (GBS) is a pathobiont that can ascend to the placenta and cause adverse pregnancy outcomes, in part through production of the toxin β‐hemolysin/cytolysin (β‐h/c). Innate immune cells have been implicated in the response to GBS infection, but the impact of β‐h/c on their response is poorly defined. We show that GBS modulates innate immune cell states by subversion of host inflammation through β‐h/c, allowing worse outcomes. We used an ascending mouse model of GBS infection to measure placental cell state changes over time following infection with a β‐h/c‐deficient and isogenic wild type GBS strain. Transcriptomic analysis suggests that β‐h/c‐producing GBS elicit a worse phenotype through suppression of host inflammatory signaling in placental macrophages and neutrophils, and comparison of human placental macrophages infected with the same strains recapitulates these results. Our findings have implications for identification of new targets in GBS disease to support host defense against pathogenic challenge.